Membrane based cross flow heat exchanger for dehumidification - Lee, Gao Ching (2015)
For tropical countries such as Singapore, removing latent load from the building is one of the primary energy consumption in the building sector. This draws to the attention of adopting membrane-based liquid desiccant air dehumidification technology due to its merit of zero liquid desiccant carryover and the capability of using waste heat or renewable solar energy as the driving heat source. Since the breakthrough discovery of the low-cost memsys® state-of-the-art novel membrane distillation technology known as Vacuum Multi-Effect-Membrane-Distillation (V-MEMD), this highly efficient thermal separation process in a compact, modular concept may become a key technology for the new revolution design of the dehumidifier. In this study, it focuses on the dehumidifier component within the developed test bed of Liquid Desiccant Air Conditioning (LDAC) system integrated with vapour compression system. Experimental investigations on the performance of all plastic membrane-based flat-type treble flow liquid desiccant dehumidifier have been carried out based on 6 input parameters. The input parameters are lithium chloride concentration, cooling water inlet flow rate, cooling water inlet temperature, air inlet flow rate, air inlet temperature and air inlet relative humidity. From the experimental results, optimum operating parameters have been determined, and the empirical equations for dehumidification process have been proposed. The empirical equations are validated with the experimental data to verify its accuracy. By using the validated empirical equations, it can be used to facilitate the process of evaluating the performance of any simulation models incorporating together with the dehumidifier.